Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1371/journal.pone.0220978
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of health care utilization of gout patients in Hawai‘i-high rates of emergency department utilization as compared to rheumatoid arthritis

Abstract: Recent and comprehensive research of gout in the Pacific region and Hawai‘i is significantly lacking. This study was conducted to improve the understanding of the healthcare utilization of gout patients within a single health care system in Hawai‘i. The objective was to examine gout inpatient, outpatient and emergency department care within a single health care system in Hawai‘i. This study was a retrospective chart review of patients, ≥ 18 years admitted to three Hawai‘i Pacific Health facilities for a primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…25 A prior study by Mak et al showed that gout care in Hawaiʻi is suboptimal, with a high number of emergency department visits compared to rheumatoid arthritis. 27 The current study supports these findings, as evidenced by suboptimal serum urate in both Native Hawaiian patients and White patients. Furthermore, the results from the current study describe a difference in emergency department and outpatient visits between Native Hawaiian and White patients, suggesting a disparity in care between the two groups.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…25 A prior study by Mak et al showed that gout care in Hawaiʻi is suboptimal, with a high number of emergency department visits compared to rheumatoid arthritis. 27 The current study supports these findings, as evidenced by suboptimal serum urate in both Native Hawaiian patients and White patients. Furthermore, the results from the current study describe a difference in emergency department and outpatient visits between Native Hawaiian and White patients, suggesting a disparity in care between the two groups.…”
Section: Discussionsupporting
confidence: 85%
“…A prior study by Mak et al showed that gout care in Hawaiʻi is suboptimal, with a high number of emergency department visits compared to rheumatoid arthritis 27 . The current study supports these findings, as evidenced by suboptimal serum urate in both Native Hawaiian patients and White patients.…”
Section: Discussionsupporting
confidence: 85%
“…The increase was most pronounced (29%) in those aged 45 to 54 years. On the other hand, a study within a single healthcare system in Hawaii reported that the rates of gout ED visits in 2017 trended downward and that they had significantly decreased since 2011 [ 10 ]. The rates of RA outpatient visits, which were used as an internal comparison group, also decreased in 2017, as did the rates of outpatient and inpatient visits for gout.…”
Section: Discussionmentioning
confidence: 99%
“…We plan to examine the factors associated with ED visits for gout patients in a future study, which would elucidate possible choices for optimization of treatment of gout and guide policy decisions. Many studies have addressed the prevalence of ED visits for gout in Western countries [ 2 , 5 , 10 , 18 20 ], but very little research has been carried out in Asian countries. The present study was the first to analyze hospital visits due to gout in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…
related quality of life (HRQoL), moderate disability (21.1%), as well as a higher cost of emergency visits. 2,4 In the US population-based cohort, older adults with gout, were more likely to have poor lower extremity function, consistent with the most common localization of affected joints. Older adults with gout were 1.18-times more likely to have poor SPPB (Short Physical Performance Battery) scores and 1.19-times more likely to have poor walking speed.
…”
mentioning
confidence: 87%